THE IMPACT OF CULTURE ON METAPHOR USAGE IN ENGLISH POLITICAL DISCOURSE - Diyora Jalilovna Narimanova (Modern American Journals, 2025)
Metaphors play an essential role in political discourse, acting as powerful rhetorical tools to shape public opinion, frame complex issues, and foster emotional connections with audiences. However, metaphor usage is not universal—it is profoundly influenced by cultural values and worldviews. This paper explores how cultural factors shape the use of metaphors in English political discourse, examining both historical and contemporary examples. By highlighting the interplay between culture and metaphor, this study underscores the need to consider cultural context when analyzing political language.
Keywords: Metaphors, political discourse, culture, framing, English language, rhetorical strategies